Pelatihan Pembuatan Stik Ikan Berbasis Bahan Dasar Lokal di Ekosistem Gambut Desa Bahaur Hulu Permai, Kabupaten Pulang Pisau - Nopembereni, Eti Dewi; Elvince, Rosana; Jaya, Adi; Maryani; Evnaweri; Subianto, Pratiwi; Saragih, Osi Karina; Adventa, Alma; Page, Susan E.; Upton, Caroline (Jurnal Pengabdian Kampus, 2024)
The aim of training activities in Bahaur Hulu Permai Village is an effort to improve the abilities and skills of people living in peat ecosystems, especially in coastal areas. Coastal areas not only have potential as fisheries resources, but also agriculture in a broad sense. The main income of coastal communities is marine fisheries and brackish water fisheries, if they are in a brackish water ecosystem. The potential for marine and river fisheries and land fisheries in Indonesia is very large. The problem is that people in coastal areas are still unable to manage natural potential into goods or products that have high economic benefits. The importance of increasing the abilities and skills of communities in coastal areas by conducting outreach, counseling and training in making fish-based food. One of the activities that can be improved is making fish sticks, in order to increase income for fishing families in particular, and coastal communities in general.